2016
DOI: 10.1016/j.solmat.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Oxide scale formation on 316L and FeCrAl steels exposed to oxygen controlled static LBE at temperatures up to 800 °C

Abstract: The corrosion behavior of three stainless steels (316L, Alkrothal 720 and Kanthal-APM) in static LBE with oxygen concentration of 10-5 wt% at temperatures of 700°C for 230 hours and 800°C for 360 hours was studied. The steel surface morphology of the oxide scales formed was investigated by SEM, XRD and Raman spectroscopy and the cross-section and by SEM and EDX. A transitional inner-layer of Fe-Cr-Al oxides was found at the substrate interface and an Al-oxide outer layer on the Fe-Cr-Al alloys. Fast growing no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The cleaning solution does not react with the oxide scale or the alloy elements. This cleaning method is adopted as a standard procedure [116] and is used by many research groups [50,56,59,117]. Following the surface evaluation using XRD and SEM/EDS, the specimens were electroplated with ∼ 40 µm nickel layer, cross-sectioned by standard metallographic techniques and further analysed by SEM/EDS.…”
Section: Samples Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The cleaning solution does not react with the oxide scale or the alloy elements. This cleaning method is adopted as a standard procedure [116] and is used by many research groups [50,56,59,117]. Following the surface evaluation using XRD and SEM/EDS, the specimens were electroplated with ∼ 40 µm nickel layer, cross-sectioned by standard metallographic techniques and further analysed by SEM/EDS.…”
Section: Samples Characterizationmentioning
confidence: 99%
“…With appropriate Cr and Al or Si concentrations, these steels are protected by a continuous, thin and slowly growing oxide scale, when exposed to oxygen-containing molten Pb and LBE [46,47]. As aluminium is especially beneficial in mitigating corrosion and excessive oxidation, researchers have focused their interest on Al-containing F/M steels [48][49][50][51][52][53][54][55][56][57][58]. An experimental criterion concerning the minimum Al concentration in Fe-Cr-Al-based ferritic alloys (C Al), valid for the chromium content (CCr) in the range 10-25 wt.%, was defined for the temperature range 400°C to 600°C: CAl = 15.3 -0.81 (CCr) + 0.0156 (CCr) 2 [wt.%] [59].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the oxide film can protect steels in LBE when the temperature is lower than 773 K, Benamati et al [21,22] also found that the oxide film is unstable at high temperature, and the austenitic AISI 316L suffered a severe corrosion attack and the dissolution of steel occurred at 823 K. Gorynin et al [24] revealed that the no effective oxide film was formed on steel surface if the oxygen concentration is lower than 10 -7 at.% in liquid lead, and the oxidation of material itself becomes a problem in maintaining an alloy in a high oxygen-containg LBE. Under different oxygen concentration, the alloys with higher Cr, Si or Al concentration can form more compact and stable oxide films, which provide better corrosion resistance in long-term, high temperature LBE experiments [9,25,26]. To improve the protective efficiency of oxide film in LBE, the effect of oxygen concentration, temperature and alloy composition on the inhibition efficiency and structure of oxide scales of the candidate materials have been the subject of considerable attention [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…We made changes in the manuscript and modified our statement (in the first paragraph of section 2. Experimental), so it reads now as following: [19]. C1-2.…”
mentioning
confidence: 99%